Long‐Term Bias Stability of the GOES‐NOP Magnetometers - S. Califf; F. J. Rich; T. M. Loto'aniu; H. J. Singer; R. J. Redmon (Earth and Space Science, 2023)
Abstract We characterize the long‐term bias stability of the GOES‐NOP series magnetometers (GOES‐13, 14, and 15) using data from 2013 through 2018. Bias stability is inferred using three methods: comparing the inboard and outboard measurements on each spacecraft, comparing the individual measurements to the TS04 magnetic field model, and comparing measurements between different GOES‐NOP spacecraft. Comparisons between the inboard and outboard magnetometers demonstrate that GOES‐14 and GOES‐15 measurements are stable within approximately 1–2 nT. The GOES‐13 inboard magnetometer has known contamination issues that hinder a useful inboard/outboard comparison, but inter‐spacecraft comparisons with GOES‐14 and GOES‐15 indicate that the GOES‐13 outboard magnetometer is also stable to 1–2 nT. Direct comparisons of each measurement to the TS04 magnetic field model support the conclusion that there is little long‐term bias drift over the 6‐year period. Model uncertainty and the variability of the field at geostationary orbit create a noise floor that is similar to the variability of the magnetometer biases. While these relative comparisons do not provide absolute measurement uncertainty, they do constrain the stability of the observations, allowing for future absolute calibration of the DC bias through different methods.